Delayed viral clearance despite high number of activated T cells during the acute phase in Argentinean patients with hantavirus pulmonary syndrome - Iglesias, Ayelén Aluminé (2022)
Background: The hallmarks of HPS are increase of vascular permeability and endothelial dysfunction. Although an exacerbated immune response is thought to be implicated in pathogenesis, clear evidence is still elusive. As orthohantaviruses are not cytopathic CD8+ T cells are believed to be the central players involved in pathogenesis. Methods: Serum and blood samples from Argentinean HPS patients were collected from 2014 to 2019. Routine white blood cell analyses, quantification and characterization of T-cell phenotypic profile, viral load, neutralizing antibody response and quantification of inflammatory mediators were performed. Findings: High numbers of activated CD4+ and CD8+ T cells were found in all HPS cases independently of disease severity. We found increased levels of some proinflammatory mediators during the acute phase of illness. Nonetheless, viral RNA remained high, showing a delay in clearance from blood up to late convalescence, when titers of neutralizing antibodies reached a high level. Interpretation: The high activated phenotypic profile of T cells seems to be unable to resolve infection during the acute and early convalescent phases, and it was not associated with the severity of the disease. Thus, at least part of the activated T cells could be induced by the dysregulated inflammatory response in an unspecific manner. Viral clearance seems to have been more related to high titers of neutralizing antibodies than to the T-cell response. Funding: This work was supported mainly by the Administración Nacional de Laboratorios e Institutos de Salud (ANLIS) “Dr. Carlos Malbrán”. Further details of fundings sources is included in the appendix.